Traditional products – vectors of sustainable development on the regional and national markets - Georgica Gheorghe; Bogdan Gabriel Nistoreanu; Alina Filip (Amfiteatru Economic Journal, 2013)
Traditional products represent an important component of the Romanian culture, of the Romanian identity, of the national heritage. In order to succeed imposing over fakes on the market, this product's regime must be very well defined and regulated by the acting legislation. While also sanctioning those who produce the so called traditional products, for which they ask a price that is usually greater, offering – not in few cases, products which can affect the consumers' health through their contents of additives or other substances that have no connection to the traditional preparation methods.
Keywords: M00; Q01; L80; C00; 330; Traditional product; sustainable development; regional development; gastronomy; business; Moldova; Muntenia; Transilvania; Banat; Oltenia; marketing research